Automated Video Analysis of Non-verbal Communication in a Medical Setting - Hart, Yuval; Czerniak, Efrat; Karnieli-Miller, Orit; Mayo, Avraham E.; Ziv, Amitai; Biegon, Anat; Citron, Atay; Alon, Uri (Frontiers in Psychology, 2016)
Non-verbal communication plays a significant role in establishing good rapport between physicians and patients and influences patient’s health outcomes. Therefore, it is important to measure and analyze non-verbal communication in medical settings. Current approaches to measure non-verbal interactions in medicine employ coding by human raters. Such tools are labor intensive and hence limit the scale of possible studies. Here, we present an automated video analysis tool of non-verbal interactions in a medical setting. We test the tool using videos of subjects that interact with an actor portraying a doctor performing one of two scripted scenarios of interviewing the subjects: in one scenario the actor was focused on his computer and briefly engaged with the subject. The second scenario included active listening by the doctor and heavy focus on the subject. We analyze the cross correlation in total kinetic energy of the two people in the dyad, and also characterize the frequency spectrum of their motion. We find large differences in interpersonal motion synchrony and entrainment between the two performance scenarios. The active listening scenario shows more synchrony and more symmetric followership than the other scenario. Moreover, the active listening scenario shows more high frequency motion termed jitter that has been recently suggested to be a marker of followership. The present approach may be useful for analyzing physician-patient interactions in terms of synchrony and dominance in a wide range of medical settings.